THE USEABLE DRIVETRAINS IN CONTEMPORARY BUS TRANSPORT (Perner's Contacts, 2021)
This paper focuses on introducing new, environmentally friendly types of drivetrains in the field of bus transport. Main goal is to present approximate costs of purchase and cost of operating (especially fuels or electricity) and connected them with real emissions of carbon dioxide for each different technology of drivetrain, including Well-to-Tank and Tank-to-Wheel emissions. The authors are using the Weighted Sum Approach method to determine currently the most suitable drivetrain for urban busses.
Keywords: alternative fuels; road transport; bus transport; carbon dioxide; Well-to-Wheel emissions